HUBUNGAN ANTARA KOMPETENSI GURU DENGAN PRESTASI BELAJAR DI SMA NEGERI 1 BARRU - Maskamiluddin, Athiyyah Shobihah; Mustamin; Subaedah; Syahid, Akhmad; Syahrul, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of teacher competence on student learning achievement in Islamic Religious Education at SMA Negeri 1 Barru. The study used a quantitative approach with a correlational research type. The study population was all 260 grade XI students of SMA Negeri 1 Barru, with a sample of 72 students taken using cluster sampling techniques and the Slovin formula. Data were collected through Likert scale questionnaires, documentation, participant observation, and interviews, with primary data sources from students and secondary data from school archives. The research instrument was tested for validity using the Product Moment formula and its reliability through Cronbach's Alpha, so that the instrument was declared appropriate and consistent for obtaining data. Data analysis was carried out using the SPSS program with the Shapiro–Wilk normality test and Pearson or Spearman correlation tests, depending on the data distribution. The results of the study indicate that teacher competence has a very strong influence on student learning achievement. Teacher competence includes pedagogical, professional, personality, and social abilities, which directly improve the quality of learning and student learning motivation. Competent teachers are able to design effective learning strategies, use a variety of methods, create a conducive learning environment, and adapt learning approaches to student characteristics. In addition to teacher competence, learning achievement is also influenced by internal student factors, such as motivation and cognitive abilities, as well as external factors, including family support, school facilities, management, and social interactions. Thus, student achievement is the result of a complex interaction between teacher competence and various other supporting factors.